Strategi Exit dan Keberlanjutan Finansial : Evaluasi Kemandirian UMKM Alumni Jakpreneur Pasca-Intervensi Pemerintah - Junaidi Hendro; Sri Handoko Sakti; Muhammad Natser (SAJMR : Southeast Asian Journal of Management and Research, 2026)
The Jakarta Entrepreneur Program (Jakpreneur) was designed as an integrated entrepreneurial ecosystem through Gubernatorial Regulation No. 2 of 2020. The program's primary focus is to transform Jakarta's MSMEs into innovative and independent business units. However, post-mentoring sustainability is crucial. This study evaluates the level of financial independence of MSMEs assisted by Jakpreneur by analyzing the implementation of the 7P framework in various regions. Through a qualitative literature review, it was found that the program's effectiveness is often hampered by "equal distribution of facilities" at the expense of "depth of intervention." The results indicate a decline in tiered participation (from registration to capital) and low levels of independent digital literacy (only 8.40% in the marketplace). Key recommendations include redesigning exit strategies based on Artificial Intelligence (AI) technology to ensure alumni remain competitive without relying entirely on government subsidies.